Linguistic and Cultural Consequences of a Second Language on Children in English Language Schools - تابان سعید, م.د; Tarza Raoof Salih, Rese (lark, 2025)
In the current era of education، a group of ideal schools in which English is studied as one of the most prominent and preferred schools are flagged by government schools، where the main language of study is English, this has an impact on the kind of language and mindset’s students.In this study، we tried to analyze theories of first and second language learning and bring back evidence in a field study. The description of the analysis is presented in two parts. The first part is dedicated to teaching and learning the first language to a child، because the first language is the foundation for learning another language. In the second part of the discussion، we tried to explain how to learn the second language and open its theories. At the end of this part in a field work، we have tried to prove in two international schools in a survey form that the second language works in the language and social aspects at a young age. Because It's obvious that language and thought are in direct communication and if it in a second language reading and speaking at a young age. Despite the fact that the process of language settle on the first language، it also affects the child's language، mind and culture. For example، in a survey question، when you ask the child، you can tell us the names of how much feast. Directly they say "Halloween and Christmas," which is clearly influenced by the language and culture of the second language. The discussion ended with a number of results and suggestions
Keywords: linguistic implications, second language, language of study